EKOLOGI KEHIDUPAN DALAM PENDIDIKAN AGAMA KRISTEN MELALUI REKONSTRUKSI NILAI BUDAYA FOSSO KEHAMILAN SEBAGAI SPIRITUALITAS MERAWAT KEHIDUPAN - Rinaldi Kefin Ogelang; Meylisa Arneta Pantow; Rani Tresya Mamaghe (Jurnal Ilmiah Wahana Pendidikan, 2026)
This article re-examines the theological and educational values ​​inherent in the Fosso-Kehamilan tradition a custom centered on pregnancy with the aim of enriching the "ecology of life" paradigm within Christian religious education. By highlighting contemporary issues such as child abuse, abortion, prenatal neglect, and the erosion of the protective spirit within families, the study emphasizes the need to adjust Christian religious education curricula. It proposes shifting the educational orientation from a model focused on cognitive aspects and doctrine toward one that places existential concern for life beginning in the womb at the core of education. Employing a qualitative approach that combines literature analysis with a critical examination of local customary values, the study reconstructs the Fosso-Kehamilan ritual from a critical biblical perspective, there by avoiding the error of viewing it merely as syncretism or a magical practice. The findings indicate that internalizing the values ​​of this tradition such as self-control, the imparting of blessings, and the sharing of responsibilities during pregnancy can serve as a foundation for contemporary Christian family education and foster a faith-based attitude from an early age. The article proposes reconstructing local culture based on theological and educational principles as a strategy for developing a relevant model of Christian religious education; such a model must be context-sensitive and capable of addressing the phenomenon of increasing disregard for the dignity of life, particularly during its earliest stages.